Management and clinical-outcome of juxta-articular osteoid osteoma lesions - Tamar Berenstein-Weyel; Gershon Zinger; Batya Jerbi; Amos Peyser; Yaacov Applbaum; Ehud Lebel (BMC Musculoskeletal Disorders)
Abstract Introduction Osteoid osteoma (OO) is a benign intra-osseous lesion. The lesion is painful and usually diagnosed by x-ray, computed tomography (CT) or magnetic resonance imaging (MRI). When the lesion is juxta-articular or intra-capsular, the symptoms may present differently than the typical OO lesion and make diagnosis more challenging. Proximity to articular cartilage may make the treatment with radiofrequency ablation more dangerous. This study presents an 11-year experience in managing juxta-articular osteoid osteoma (JAOO) including long-term follow-up, while using CT-guided radiofrequency ablation (CT-RFA). Methods All patients diagnosed with OO and managed with CT-RFA between 2010 and 2020 were reviewed. Those with a lesion that was intra-capsular or less than 2 cm from the articular cartilage were included. Charts and all imaging studies were evaluated, and patients were interviewed by phone for any persistent or recurrent symptoms. Results There were 168 patients with OO during this period and 59 met the criteria for inclusion. Forty-four (75%) were male and median age at the time of ablation was 20.7 years (range 3–59 years). Thirteen (22%) had active growth plates during ablation. Three patients (5%) required a repeat ablation for non-resolving pain. None of the 13 children with open physes had growth disturbance of the affected limb after ablation. In 3 patients, the typical OO pain resolved but an activity related pain persisted. One of them had articular damage that may be related to the CT-RFA. Conclusion JAOO may present challenges for diagnosis and treatment and CT-RFA is the current standard for treatment. Despite proximity to the cartilage and physis, careful attention to technique showed only one injury to these structures in this series of 59 patients.